The Impact of COVID-19 on Social Isolation in Long-term Care Homes: Perspectives of Policies and Strategies from Six Countries - Chu, Charlene H.; Wang, Jing; Fukui, Chie; Staudacher, Sandra; A. Wachholz, Patrick [UNESP]; Wu, Bei (Taylor & Francis, 2021)
Preventing the spread of COVID-19 in long-term care homes is critical for the health of residents who live in these institutions. As a result, broad policies restricting visits to these facilities were put in place internationally. While well meaning, these policies have exacerbated the ongoing social isolation crisis present in long-term care homes prior to the COVID-19 pandemic. This perspective highlights the dominant COVID-19 LTC policies from six countries, and proposes five strategies to address or mitigate social isolation during the COVID-19 pandemic that can also be applied in a post-pandemic world.
Keywords: COVID-19; international; long-term care; nursing home; social isolation